A Novel Security Model for Cooperative Virtual Networks in the IoT Era - Alabady, Salah A.; Al-Turjman, Fadi; Din, Sadia (International journal of parallel programming, 2020)
The Internet of Things (IoT) has particular applications in public safety as well as other domains such as smart cities, health monitoring, smart homes and environments, smart industry, and various types of pervasive systems. The attacker can simply attack the IoT device in such applications, because it is randomly distributed, dynamic topology and not reliable due to energy and communication limitation. Moreover, the threat to confidentiality and security is increasing as the number of devices connected in IoT is increasing. As the numbers of devices connected to the Internet is expanding, the threat to confidentiality and security is increasing. The aim of this paper is design a typical network security model for cooperative virtual networks in the IoT era. This paper presents and discusses network security vulnerabilities, threats, attacks and risks in switches, firewalls and routers, in addition to a policy to mitigate those risks. The paper provides the fundamentals of secure networking system including firewall, router, AAA server and VLAN technology. It presents a novel security model to defense the network from internal and external attacks and threats in the IoT Era. A testbed is built to investigate the proposed model, and the performed assessment show an effective security performance with a good network performance.